2005
DOI: 10.1093/humrep/deh588
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combination therapy with metformin and combined oral contraceptives (COC) versus COC alone on insulin sensitivity, hyperandrogenaemia, SHBG and lipids in PCOS patients

Abstract: Adding metformin slightly modified the treatment effect of COC, causing a more significant decrease in the free androgen index but having no additional positive impact on lipids, insulin sensitivity, SHBG or testosterone. The available data do not offer enough evidence to advocate the standard use of combined treatment in PCOS. Whether the combination might be beneficial for specific subgroups of patients is of further interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 21 publications
4
56
1
4
Order By: Relevance
“…A prospective study (335) designed to evaluate the effects of metformin plus flutamide on metabolic parameters and insulin resistance in nonobese women with PCOS showed a similar reduction in free testosterone after administration of both 2250 mg/d metformin and 250 mg/d flutamide. In addition, metformin plus OCs provided benefits on hyperandrogenism and insulin resistance in nonobese PCOS women not desiring pregnancy, but the effects on central adiposity and dyslipidemia were weaker (336). Recent studies showed that the combination of metformin and low-dose flutamide was related to endocrine and metabolic benefits in nonobese (337,338) and obese (339) PCOS patients by acting on the upstream abnormalities of PCOS without merely masking downstream symptoms such as OCs.…”
Section: Hyperandrogenismmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study (335) designed to evaluate the effects of metformin plus flutamide on metabolic parameters and insulin resistance in nonobese women with PCOS showed a similar reduction in free testosterone after administration of both 2250 mg/d metformin and 250 mg/d flutamide. In addition, metformin plus OCs provided benefits on hyperandrogenism and insulin resistance in nonobese PCOS women not desiring pregnancy, but the effects on central adiposity and dyslipidemia were weaker (336). Recent studies showed that the combination of metformin and low-dose flutamide was related to endocrine and metabolic benefits in nonobese (337,338) and obese (339) PCOS patients by acting on the upstream abnormalities of PCOS without merely masking downstream symptoms such as OCs.…”
Section: Hyperandrogenismmentioning
confidence: 99%
“…Only one clinical trial comparing 6 months of OCs (35 g E2 combined with 250 g norgestimate in a cyclic regimen of 21 d of active pills followed by a 7-d pill-free interval) alone vs. OCs combined with 1500 mg/d metformin reported no significant difference in body weight (336). Finally, metaanalysis (190) of two studies investigating OCs alone vs. OCs combined with metformin again revealed no difference in BMI between groups.…”
Section: Obesitymentioning
confidence: 99%
“…Furthermore, pills with different E 2 dosages and type of progestins have been used. The outcome of these studies was extremely variable and showed improvements, no changes, development of glucose intolerance, or type 2 diabetes (28)(29)(30)(31). In common with other OCs, the pill containing EE and drospirenone seems to impair insulin resistance (26,32).…”
Section: Figurementioning
confidence: 99%
“…Ibañez et al 27 noted that combining flutamidemetformin and an oral contraceptive containing drospirenone reduces the levels of adipocytokines, triglycerides and abdominal fat, suggesting that adding metformin to the therapy is beneficial compared to using a contraceptive alone. Cibula et al, 28 in turn, comparing the use of oral contraceptives combined or not with metformin, failed to demonstrate a significant additional benefit regarding lipids, insulin sensitivity, SHBG and testosterone when the medications were combined.…”
Section: Discussionmentioning
confidence: 99%